Foreword - Epure, Manuela (Journal of Economic Development, Environment and People, 2017)
Recently, the World Economic Forum Annual Meeting took place from 17-20 January 2017 at Davos-Klosters, Switzerland and then key topic was Global Governance and the related issues such as: Fourth Industrial Revolution, responsive and responsible leadership, restoring economic growth and global collaboration.[1] Important changes are expected regarding size, speed and scope of these transformations that Fourth Industrial Revolution generated. The transformations consist mainly of new systems built on the infrastructure of the digital revolution. Also, this will fundamentally change the way in which we produce, consume, move, communicate and interact with one another. Nanotechnologies and given new powers of genetic engineering will impact dramatically who we are and how we think and behave[2] .